Ocular and Systemic Risk Factors of Different Morphologies of Scotoma in Patients with Normal-Tension Glaucoma - Ewa Kosior-Jarecka; Dominika Wróbel-Dudzińska; Urszula Łukasik; Tomasz Żarnowski (Journal of Ophthalmology)
The Aim. The aim of this study was to assess general and ocular profiles of patients with single-localisation changes in visual field. Material and Methods. The study group consisted of 215 Caucasian patients with normal-tension glaucoma with scotoma on single localisation or with preperimetric glaucoma. During regular follow-up visits, ophthalmic examination was carried out and medical history was recorded. The results of the visual field were allocated as paracentral scotomas, arcuate scotomas, peripheral defects, or hemispheric defects. Statistical analysis was conducted with Statistica 12, and p<0.05 was considered statistically significant. Results. Risk factors such as notch, disc hemorrhage, general hypertension, migraine, and diabetes were strongly associated with specific visual field defects. Paracentral defect was significantly more frequent for women (p=0.05) and patients with disc hemorrhage (p<0.001). Arcuate scotoma occurred frequently in patients without disc hemorrhage (p=0.046) or migraines (p=0.048) but was observed in coexistence with general hypertension (p<0.001). The hemispheric defect corresponded with notch (p=0.0036) and migraine (p=0.081). Initial IOP was highest in patients with arcuate scotoma and lowest in patients with preperimetric glaucoma (p=0.0120). Conclusions. The specific morphology of scotoma in patients with normal-tension glaucoma is connected with definite general and ocular risk factors.